1997
DOI: 10.1136/jnnp.63.1.4
|View full text |Cite
|
Sign up to set email alerts
|

X linked adrenoleukodystrophy: clinical presentation, diagnosis, and therapy

Abstract: X linked adrenoleukodystrophy (X-ALD)is an inherited disorder of peroxisomal metabolism, biochemically characterised by accumulation of saturated very long chain fatty acids. Accumulation of these fatty acids is associated with cerebral demyelination, peripheral nerve abnormalities, and adrenocortical and testicular insuYciency. The lowest estimated birth incidence is one per 100 000. At least six phenotypes can be distinguished, of which the two most frequent are childhood cerebral ALD and adrenomyeloneuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
101
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 121 publications
4
101
0
7
Order By: Relevance
“…Moser (1) reported that the prevalence of X-linked ALD was between one in 20,000 and one in 100,000 male births, and a European survey reported that the prevalence of this disease was at least one in 100,000 male births, with an overall prevalence of at least one in 200,000 (15). X-linked ALD has been identified in patients from all races and continents, with no apparent predilection for any one race (15).…”
Section: Clinical Manifestations Of X-linked Aldmentioning
confidence: 99%
“…Moser (1) reported that the prevalence of X-linked ALD was between one in 20,000 and one in 100,000 male births, and a European survey reported that the prevalence of this disease was at least one in 100,000 male births, with an overall prevalence of at least one in 200,000 (15). X-linked ALD has been identified in patients from all races and continents, with no apparent predilection for any one race (15).…”
Section: Clinical Manifestations Of X-linked Aldmentioning
confidence: 99%
“…After fatty acid addition to the cells, a general decrease in [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]acetate incorporation into total fatty acids as well as into cholesterol was detected (Fig. 2).…”
Section: Effect Of Exogenously Added Fatty Acids On Fatty Acids and Cmentioning
confidence: 99%
“…The biosynthesis and deposition of lipids play an important role in maintaining brain structure and function, for example, during development-associated biogenesis of neural cell membranes. It is well established that alterations in lipid metabolism are the cause of or are associated with many neurological diseases (1)(2)(3).…”
mentioning
confidence: 99%
“…A few elderly males with mild symptoms have been reported 7, 8, 9, 10, but descriptions detailing symptoms and features in this subset of patients are lacking. The existence of such phenotypes is important, both for the counseling of young males diagnosed with X‐ALD on the basis of genetic studies, and for the further investigation of X‐ALD kindreds searching for affected males who may form a link to other affected branches of the pedigree.…”
Section: Introductionmentioning
confidence: 99%